Prevalence of Pre-Existing Corneal Astigmatism in Age Related Cataract Patient (Faridpur Medical College Journal, 2013)
Cataract surgery is no more a blind rehabilitation surgery, it absolutely gives normal vision. In the era of modern cataract surgery patients expectations are also high about visual outcome. This prospective study was carried out to investigate the magnitude and pattern of pre-existing corneal astigmatism in age related cataract patient at Faridpur Medical College Hospital, Faridpur and Agha Yusuf Adhunik Hospital, Kustia, from July 2009 to June 2012. We examined 850 eyes of 730 patients who underwent cataract surgery. The mean age at the time of surgery was 61.9±8.1 (40 to 70) years. Corneal astigmatism was measured by Auto Refracto Keratometer at least two times for each patient. Astigmatism was calculated from diopteric difference of vertical reading from horizontal reading. With the rule (WTR) astigmatism was considered when steep meridian at 90°± 20°. Against the rule (ATR) astigmatism was considered when steep meridian at 180°±20°. Astigmatism is in other direction is defined as oblique. On keratometry, when vertical reading (k1) was found greater than horizontal (k2) was considered WTR astigmatism and the reverse reading for ATR astigmatism. The percentage of corneal astigmatism was 1D or less was 69.6%, more than 1D and less than 1.5D, 27.6% and more than 1.5D and less then 2D 2.8%. Prevalence of ATR astigmatism was more than WTR astigmatism and prevalence of ATR astigmatism increases significantly with age. Approximately two third of pre-operative patient had 1D or less astigmatism and one third had more than 1D corneal astigmatism. DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16887 Faridpur Med. Coll. J. 2013;8(1): 02-04